Medicinal plants used by the tribal communities of Thanchi Upazila in Bandarban Hill District, Bangladesh (Asian Journal of Medical and Biological Research, 2022)
Medicinal plants play in an important role in the primary health care system. The paper deals with the indigenous knowledge related to ethnomedicinal knowledge and plant parts application for curing various ailments by the ethnic community of Thanchi Upazila of Bandarban Hill District. Semi-structured questionnaires, interviews, group discussions, and specific plant sample collection were done from July 2019 to December 2021 to procure ethno-medicinal data from local herbalists and elderly villagers for this study and from the forest areas. A total of 129 plant species under 110 genera and 63 families have been documented, which have been traditionally used by the ethnic people for the treatment of different ailments. Traditional knowledge and information about medicinal plants such as local names, scientific names, families, habits, habitats, plant-parts used, names of ailments, modes of use, etc. were recorded, validated, and documented. Plant families namely, Asteraceae and Euphorbiaceae were represented by the highest (8) number of species, followed by Fabaceae, Verbenaceae, Apocynaceae, Araceae, Caesalpiniaceae, Lamiaceae, Rubiaceae and Zingiberaceae. The most widely used medicinal plants included Anacardium occidentale, Bombax ceiba, Calotropis gigantea, Terminalia chebula, Aegle mermelos, Ageratum conyzoides, Andrographis paniculata, Aristolochia indica, Blumea balsamifera, Bryophyllum pinnatum, Celosia cristata, Centella asiatica, Melastoma malabathricum, Mimosa pudica, Musa paradisiaca, Oroxylum indicum, Plumbago indica and Vitex negundo. Herbs (36%) were found to be the most used plant, followed by shrubs (33%), trees (17%), climbers (9%) and fern (5%). Most medicinal plants were used for the treatment of fever, skin diseases, cough problems, menstrual problems, body pain, indigestion, headaches, stomachaches, constipation, swelling problems, wounds and others. Among the plant parts, mostly leaves were used (43%), followed by roots (21%), whole plants (10%), stems (6%) along with fruit, rhizome, flower, bark, seed and latex for the treatment of diseases. The most common formulations prescribed to treat various diseases were juices. The findings will be useful for future research in the Bandarban Hill District.Asian J. Med. Biol. Res. 2022, 8 (2), 123-140